’Black, Brown and Beige’ and the politics of Signifyin(g): Towards a critical understanding of Duke Ellington - Burrows, George (Jazz Research Journal, 2007)
Duke Ellington has attracted critical attention from across the whole cultural spectrum and yet he is in many ways a problematic figure who remains misunderstood. This paper draws on Michel Foucault’s consideration of polemics to illuminate critical strategies that have been directed towards Ellington. It explores how we might move beyond polemics and reinterpret Ellington as an artist ‘beyond category’ by considering his most controversial and ambitious work, Black, Brown and Beige, as a Signfyin(g) text. Ellington’s unique working practices, the special sound world of his band, his declared tendency to ‘say things without saying them’ and his view of himself as a black bandleader-composer of ‘Negro folk music’ all help inform a reassessment of the work in light of recent developments in African-American critical thinking and to establish the political legacy of Ellington’s cultural positioning as a trickster figure critiquing polemics by slipping between, about or around musical categories.